2014
DOI: 10.15288/jsad.2014.75.901
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Social Host Laws and Underage Drinking: Findings From a Study of 50 California Cities

Abstract: ABSTRACT. Objective: Many states and local communities have enacted social host (SH) laws to reduce underage drinking in private settings. However, little is known about whether such laws are effective. This study examined relationships between city SH laws and underage drinking in general and at parties in private settings. Method: SH policy data were collected for 50 California cities in 2009, and SH policies were rated for comprehensiveness and stringency. Annual telephone interviews were conducted with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Adolescents were selected and recruited through a two-stage process. First, a subset of 24 cities was selected from an existing geographically diverse sample of 50 noncontiguous California cities (population range: 50,000 to 500,000) Paschall et al, 2014). The 24 cities were selected based on high levels of underage drinking, drinking and driving, and alcohol-related motor vehicle crashes using data from various sources, including the California Healthy Kids Survey (WestEd, 2016), a survey of more than 8,000 adults conducted by the Prevention Research Center , and the California Statewide Integrated Traffic Reporting System (California Highway Patrol, 2016).…”
Section: Study Sample and Survey Methodsmentioning
confidence: 99%
“…Adolescents were selected and recruited through a two-stage process. First, a subset of 24 cities was selected from an existing geographically diverse sample of 50 noncontiguous California cities (population range: 50,000 to 500,000) Paschall et al, 2014). The 24 cities were selected based on high levels of underage drinking, drinking and driving, and alcohol-related motor vehicle crashes using data from various sources, including the California Healthy Kids Survey (WestEd, 2016), a survey of more than 8,000 adults conducted by the Prevention Research Center , and the California Statewide Integrated Traffic Reporting System (California Highway Patrol, 2016).…”
Section: Study Sample and Survey Methodsmentioning
confidence: 99%
“…Paschall, Lipperman‐Kreda, Grube, and Thomas () noted, for example, that effectiveness of social host laws in California in preventing or reducing under‐age drinking depend “not only on the content of the laws but also on public awareness and enforcement.” Likewise, Jones‐Webb, Toomey, Lenk, Nelson, and Erickson () found that social host policies were more likely to be implemented in communities that prioritized prevention of underage drinking and had a full‐time law enforcement position devoted to underage drinking. Policymakers, the media, and the general public need to become aware of the scope of harm from alcohol, the relatively low levels of consumption at which risk is elevated, and that it is not only the patterns of dependent drinkers that contribute to population‐level problems.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Paschall et al (2014) found that a stronger social host policy did not reduce past-year alcohol use or heavy drinking in general among past-year drinkers but was inversely related to drinking at parties. Holder et al (2000) found decreases in the number of nighttime injury crashes (10%), the number of crashes in which the driver had been drinking (6%), and the number of assault injuries observed in emergency departments (43%) in three California communities with environmental interventions compared with three comparison cities.…”
Section: Discussionmentioning
confidence: 99%